The Conception of the Body of Slaves and Dependents in the Greek World - Plácido, Domingo (Res Publica. Revista de Historia de las Ideas Políticas, 2017)
The image of body of the individuals who mould society seems like a mirror of the idea of persons in every moment. The body is characterized very early as a antithesis to spiritual life who defines the person plenty considered and with all the rights. Changes affect to peasant subjected till chattel slavery is imposed, which marks maxim alterity between human beings. Inside such idea, symptoms of evolution are detected until roman domination.
Keywords: History of the body; Greece; slavery.